Operational Analysis and Potential Tourist Attraction of Villa Flamboyan 98 in Kiarapedes, Purwakarta - Rizal Hidayat; Firdaus Azhar (Journal Tourism Nomic, 2025)
Villa Flamboyan 98 is one of the tourist accommodations located in the mountainous area of Kiarapedes, Purwakarta, West Java. With a cool, calm, and beautiful natural atmosphere, this villa is an attraction for tourists who want a relaxing experience in the middle of nature. This study aims to evaluate the operational aspects of Villa Flamboyan 98 through direct observation which includes location, facilities, services, and potential development as a tourist destination. The observation results show that this villa has a number of advantages such as a clean and natural environment, comfortable building design, and friendly and responsive staff service. The facilities available are quite adequate, including bedrooms, kitchens, living rooms, and garden areas. However, there are several weaknesses that need to be considered, including inadequate road access for four-wheeled vehicles and limited modern entertainment facilities for guests. These findings show that although Villa Flamboyan 98 already has a strong foundation as a nature-based tourist accommodation, some strategic improvements need to be made to increase customer attraction and satisfaction. The recommendations are aimed at strengthening infrastructure, improving facilities, and promoting more effectively in order to be able to compete in the local and regional tourism market